2014
DOI: 10.4236/ojss.2014.41003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NaCl-Induced Salinity and Human Urine Fertilization on Substrate Chemical Properties

Abstract: We evaluated the effect of NaCl-induced salinity and successive urine fertilization on changes in cultivation substrate chemical properties in a greenhouse study. The substrate was composed of an equal volume ratio mixture of bio-waste compost, quartz sand and silty loam soil. Salinity was imitated by adding NaCl solutions to a known substrate weight achieving three target salinity treatments of EC e 1.3 (S0-no NaCl), 4.6 (S1) and 7.6 (S2) dS•m −1. Cultivation substrate had been cropped with two cycles of maiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…However, crops under the U3 treatment did not take up more sodium than under the other treatments (Table 3S, Supplementary data), and the soil salinity was still below the spinach salt tolerance threshold established at 9.4 dS m −1 by Ferreira et al (2018); so, it is unlikely that the spinach crops underwent a saline stress. Other studies on urine fertilization confirm that critical values of soil conductivity are only observed when urine is applied in excess (up to 13 dS m −1 with 800 kgN ha −1 ) (Boh and Sauerborn 2014;Mnkeni et al 2008;Neina 2013) and that the crop response depends on its salt tolerance threshold (Mnkeni et al 2008). Nevertheless, the effects of urine fertilization on soil salinity have not been investigated so far for longer than one or two cropping seasons.…”
Section: Effect Of Urine Fertilization On Soil Ph and Salinitymentioning
confidence: 84%
See 1 more Smart Citation
“…However, crops under the U3 treatment did not take up more sodium than under the other treatments (Table 3S, Supplementary data), and the soil salinity was still below the spinach salt tolerance threshold established at 9.4 dS m −1 by Ferreira et al (2018); so, it is unlikely that the spinach crops underwent a saline stress. Other studies on urine fertilization confirm that critical values of soil conductivity are only observed when urine is applied in excess (up to 13 dS m −1 with 800 kgN ha −1 ) (Boh and Sauerborn 2014;Mnkeni et al 2008;Neina 2013) and that the crop response depends on its salt tolerance threshold (Mnkeni et al 2008). Nevertheless, the effects of urine fertilization on soil salinity have not been investigated so far for longer than one or two cropping seasons.…”
Section: Effect Of Urine Fertilization On Soil Ph and Salinitymentioning
confidence: 84%
“…Thus, it could represent a complete fertilizing solution even though the bioavailability of urine micronutrients has not been well documented (Olivia et al 2015). Yet, the high concentrations in Na + , Cl − and SO 4 2− could also cause soluble salt accumulation in soils (Boh and Sauerborn 2014;Mnkeni et al 2008;Shingiro et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the high concentration in Na + , Cl − and SO 4 2− could also cause salt accumulation in soils. A few studies (Boh and Sauerborn, 2014;Mnkeni et al, 2008;Shingiro et al, 2019) have reported an increase in soil conductivity after urine application, suggesting that urine fertilisation can cause the build-up of soluble salt concentrations in soils.…”
Section: Introductionmentioning
confidence: 99%